Expanding the clinical spectrum of dermal hyperneury: report of nine new cases and a review of the literature. Issue 5 (6th September 2019) - Ieremia, Eleni; Marušić, Zlatko; Mudaliar, Vivek; Kelly, Susan; Gonzalvo Rodriguez, Pablo; McNiff, Jennifer M; LeBoit, Philip E; Calonje, Eduardo
Abstract : Aims: Dermal hyperneury is defined as the hypertrophy of small nerves in the dermis. It has been described in a variety of settings. We present a series of nine new cases with a distinctive clinical presentation and review the existing literature. The aim of the study was to summarise the clinical, histopathological and immunohistochemical findings in a case series of dermal hyperneury with unique clinical presentation. Methods and results: Nine cases were identified from the referral practice of one of the authors. Clinical characteristics, including demographic details, were collated. The histopathological features and novel immunohistochemical findings were analysed. Four cases presented with multiple skin lesions. Clinical evaluation revealed no associated syndromic stigmata. The histology in all cases was that of dermal hyperneury. Immunohistochemistry for phosphatase and tensin homologue (PTEN) and RET was supportive of the lack of syndromic association. Conclusion: The presentation of dermal hyperneury with multiple cutaneous lesions and no syndromic associations is distinctive, and no study with PTEN and RET immunohistochemistry has previously been reported. Comparisons with recent reports of multiple non‐syndromic mucocutaneous neuromas are discussed.